Choice of the technical devices structure for safety systems - V. M. Alefirenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The method of the technical devices structure choice for safety systems with the usage of complex assessment of their quality level on the example of video surveillance system is offered. The results of quality complex indicators calculations of the technical devices which are a part of video surveillance system are given.